(untitled) (MMIT Proceedings, 2025)
The article examines the fundamental factors determining the effectiveness of fundamental and applied research conducted by the university. In an era of rapid scientific and technological development, the quality of education is regarded as one of the key factors shaping the competitiveness of both individual specialists and nations as a whole. The interaction between science and the educational process plays a crucial role in training highly qualified professionals and modernizing curricula. The successful integration of scientific research into educational practice demonstrates a steady improvement in students’ knowledge and skills, while also fostering a deep understanding of research methodology. The article further analyzes various aspects, including the relationship between fundamental and applied research and educational outcomes, as well as their impact on establishing a scientific foundation for effective managerial decision-making.